(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The modern practice of social work in Ukraine has been forced to receive a strong impetus for development, which requires a deep understanding of the nature of people’s prolonged experience, large-scale emergencies related to armed conflict and political instability, and a revision of the forms and methods of work in such situations. The focus of the article is on support groups as a method of psychosocial assistance in coping with ongoing traumatic event. The article presents the results of a study that demonstrates the dynamics, impact, and effectiveness of support groups in psychosocial assistance to individuals affected by the ongoing war. The study is centered on the experience of support groups in the period from March 2022 to April 2023 – a period marked by the immense stress of the first year of the full-scale Russian-Ukrainian war – for such target audiences as persons affected by the war (a significant proportion of whom experienced forced migration) and women whose partners perform military service. Methods. Within the framework of the phenomenological paradigm, the method of thematic analysis of 106 reports from support group facilitators and a questionnaire survey of 13 support group participants was used. Results. Through a thematic analysis, the study identified the needs of group participants and ways to overcome the stress of war on their own and through participation in support group meetings. Two key focuses of discussion present in each meeting were identified: “What are you worried about?” and “How can you support yourself?”. The significant influence of the contextual factor on the course of the processes of living with an ongoing traumatic event by participants of support groups was revealed. In the identified six time periods, the key feature of the period change was the events at the frontlines and political violence against civilians by the aggressor. Despite the shared general context of the war, there are differences in the difficulties and needs of representatives of different groups – people who have been affected by the war generally and those whose family members are directly involved in military actions. A survey additionally confirms the positive impact of participation in groups on their psycho-emotional state. Conclusions. The results show that support groups based on the resilience approach provide a safe and comfortable environment where participants can discuss their experiences, receive various types of support, and develop their protective characteristics and ability to use new methods of overcoming life difficulties (from the ability to maintain own psycho-emotional state, regain control and manage their situation to strengthening their own identity, awareness of themselves as Ukrainians and part of a community).